2008
DOI: 10.1111/j.1365-246x.2008.03828.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the theoretically predicted seismo-magnetic conversion

Abstract: We acknowledge the Geophysical Journal International and the Association/Society and Blackwell Publishing. The definitive version is available at www.wileyinterscience.com. The reference is : Bordes, C., L. Jouniaux, S. Garambois, M. Dietrich, J.-P. Pozzi, and S. Gaffet, Evidence of the theoretically predicted seismo-magnetic conversion, G.J.I., 174, issue 2, 489-504, doi:10.1111/j.1365-246X.2008.03828.xInternational audienceSeismo-electromagnetic phenomena in porous media arise from seismic wave-induced fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 73 publications
(106 reference statements)
1
60
0
Order By: Relevance
“…These effects have been verified experimentally in the laboratory (e.g., Zhu et al, 1999Zhu et al, , 2000Zhu & Toksöz, 2003;Block & Harris, 2006;Bordes et al, 2006) and in the field (e.g., Long & Rivers, 1975;Butler et al, 1996;Mikhailov et al, 1997;Beamish, 1999;Garambois & Dietrich, 2001;Dupuis et al, 2007;Haines et al, 2007). Also, the coseismic magnetic fields associated with a Stoneley wave (Zhu & Toksöz, 2005) and with a shear wave have been measured (Bordes et al, 2006(Bordes et al, , 2008. Electrokinetic theory combines poroelastic and EM theory through coupling in flux/force relations.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…These effects have been verified experimentally in the laboratory (e.g., Zhu et al, 1999Zhu et al, , 2000Zhu & Toksöz, 2003;Block & Harris, 2006;Bordes et al, 2006) and in the field (e.g., Long & Rivers, 1975;Butler et al, 1996;Mikhailov et al, 1997;Beamish, 1999;Garambois & Dietrich, 2001;Dupuis et al, 2007;Haines et al, 2007). Also, the coseismic magnetic fields associated with a Stoneley wave (Zhu & Toksöz, 2005) and with a shear wave have been measured (Bordes et al, 2006(Bordes et al, , 2008. Electrokinetic theory combines poroelastic and EM theory through coupling in flux/force relations.…”
Section: Introductionmentioning
confidence: 96%
“…A wide range of field and laboratory measurements of the coseismic and interface response fields was presented (see e.g., Martner & Sparks, 1959;Thompson & Gist, 1993;Butler et al, 1996;Mikhailov et al, 1997;Beamish, 1999;Zhu et al, 1999;Mikhailov et al, 2000;Zhu et al, 2000;Garambois & Dietrich, 2001;Zhu & Toksöz, 2003, 2005Block & Harris, 2006;Bordes et al, 2006;Dupuis & Butler, 2006;Haines et al, 2007;Dupuis et al, 2007;Strahser et al, 2007;Liu et al, 2008;Zhu et al, 2008a,b;Dupuis et al, 2009). Zhu & Toksöz (2005) and Bordes et al (2006Bordes et al ( , 2008 reported on coseismic magnetic field measurements associated with a Stoneley wave and a shear wave, respectively. The inverse effect was also measured.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Note that it has been already suggested to monitor the magnetic field in boreholes to detect fluid flow variations in an accretionary prism . Bordes et al (2006Bordes et al ( , 2008 showed the existence of seismomagnetic conversions, predicted by the theory since 1994. The authors developed an experimental set-up with a remotecontrolled seismic source, to induce seismic wave propagation in a saturated sand column (Fig.…”
Section: Seismo-magnetic Detectionmentioning
confidence: 99%
“…When performing magnetic measurements it is necessary to use nonmetallic materials, because of their possible even small displacements within the ambient magnetic field. Measurements performed on dry samples showed that both the electric field and the magnetic field are within the noise level (Zhu et al, 2000;Bordes et al, 2008).…”
Section: Laboratory Observationsmentioning
confidence: 99%
See 1 more Smart Citation